Study of Planned Maintenance System Senior Admiral John Lie’s Training Ship on Shipping Safety - Ansar, Azhar Ariansyah; Luasunaung, Alfret; Sumilat, Deiske Adeliene; Pamikiran, Revols Dolfi Ch; Kaparang , Frangky Erens; Onibala, Hens (Sam Ratulangi University, 2023)
The implementation of the ship maintenance management system on Rear Admiral Jhon Lie's training ship did not run optimally, which impacted the less-than-optimal condition of various training ship equipment because the crew did not carry out the ship maintenance system according to the procedure, resulting in the incident that the ship's anchor winch operation did not function optimally when the ship was anchored in Belang Port, Southeast Minahasa. This study aims to identify and analyze the positive and significant effect of the planned maintenance system on shipping safety. The primary data collection methods used in this study were questionnaires and interviews. In this study, data processing and presentation were in the form of diagrams and path analysis with structural equation modeling (SEM-PLS) using SmartPLS. From the results of the data analysis, the R-square value of shipping safety (Y) is 0.307, which means that the planned maintenance system (X1) and ship maintenance (X2) can affect shipping safety (Y) by 30.7%. Ship maintenance (X2) has a significant effect on sailing safety (Y), with P-values = 0.033 0.05 (hypothesis accepted). The planned maintenance system (X1) has a significant effect on sailing safety (Y), with a P-value of 0.037 0.05 (hypothesis accepted). As a result of the analysis, it was found that the planned maintenance system has a significant effect on shipping safety.